Hubungan antara Stres Akademik dengan Motivasi Belajar dalam Pembelajaran Daring pada Mahasiswa - Ayuni, Putri; Sofah, Rahmi (diterbitkan oleh Program Studi Bimbingan dan Konseling FKIP Universitas Sriwijaya Jl. Palembang Prabumulih KM 3.2 Palembang-Indonesia Email: jkk@fkip.unsri.ac.id, 2022)
This research aims to determine the relationship between academic stres and learning motivation in online learning for guidance and counseling students of FKIP Unsri. This research uses the correlational quantitative method. The population of this study was 80students in the 2019 class. The sample was taken using total sampling technique so the sample was 80 students. Data collection technique that use in this research is questionnaire via google form. Data analysis that used ini this research is Pearson-Product Moment with the help of SPSS version 25. The results of the data analysis showed the correlation coefficient (rcount) rxy = 0,394 and rtable 0,219 which means rcount > rtable (0,394 > 0,219), it show that there is a negative significant relationship between academic stres and learning motivation in online learning for guidance and counseling FKIP Unsri students, which means if academic stress getting high, it will decreased student’s learning motivation.